1978
DOI: 10.1113/jphysiol.1978.sp012392
|View full text |Cite
|
Sign up to set email alerts
|

A study of the routes by which protein passes from the pericardial cavity to the blood in rabbits.

Abstract: SUMMARYThe routes by which radioiodinated serum albumin placed in the pericardial cavity gains access to the circulation have been investigated in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…He underwent percutaneous nephrostomy followed by left nephrectomy with complete resolution of pleural and pericardial effusion and the pleural draining catheter was removed uneventfully. The common embryologic development of the pleuropericardial cavities and the existing lymphatic communications of the pleura, pericardium and diaphragm might be the pathogenetic mechanism responsible for the formation of secondary pericardial effusion in our case 3. The complete resolution of the pericardial effusion without the need for drainage after the urology procedure further establishes its direct relationship with the obstructive uropathy.…”
supporting
confidence: 50%
“…He underwent percutaneous nephrostomy followed by left nephrectomy with complete resolution of pleural and pericardial effusion and the pleural draining catheter was removed uneventfully. The common embryologic development of the pleuropericardial cavities and the existing lymphatic communications of the pleura, pericardium and diaphragm might be the pathogenetic mechanism responsible for the formation of secondary pericardial effusion in our case 3. The complete resolution of the pericardial effusion without the need for drainage after the urology procedure further establishes its direct relationship with the obstructive uropathy.…”
supporting
confidence: 50%
“…The potential role of the parietal pericardium had been generally neglected until recently when evidence has accumulated that it might serve as a major route (2,3). The parietal pericardium in the dog and rabbit has a low resistance to bulk transfer of liquids (4).…”
Section: Discussionmentioning
confidence: 99%
“…As some pericardial fluid is produced by the parietal pericardium and because the fluid is removed by parietal pericardial lymphatics, disease of the parietal pericardium (viral pericarditis) can cause pericardial effusions. Gibson and colleagues 8 showed that radiolabelled albumin can migrate directly from the pericardial to the pleural space in rabbits. Furthermore, in mice and hamsters, 50 µm pores directly connecting the pericardial and pleural spaces 9 have been demonstrated on ultrastructural examination, which allow free passage of particulate matter from the pleural to pericardial space 10 .…”
Section: Discussionmentioning
confidence: 99%